TATA KELOLA DAN PENGEMBANGAN PARIWISATA GEOPARK PONGKOR KABUPATEN BOGOR TERHADAP PENINGKATAN EKONOMI MASYARAKAT - Sanjaya, Sandi; Rahmawati, Rita; Sudarsa, Agus Suarman (Universitas Djuanda, 2022)
Geopark is an area with geological elements where the local community is expected to participate in protecting and improving the function of natural heritage, including its archaeological, ecological and cultural values. Biodiversity (Biodiversity), and Cultural Diversity (Cultural Diversity), and managed for conservation, education, and sustainable community economic development with the active involvement of the community and local government, therefore, in this case, the development of the Pongkor geopark is considered very important for improving its exceptional regional economy in the district of Bogor. The purpose of this study aims to determine the effect of governance and tourism development on improving the community's economy, this study uses a quantitative research approach with descriptive associative methods. This research was conducted on the managers of the Geopark Pongkor Bogor Regency, and data were obtained from the distribution of questionnaires to 46 managers of the Geopark Pongkor Bogor Regency. The results of this study indicate the need for improvement in governance and tourism development, especially in the Pongkor geopark, Bogor district.